HUBUNGAN KONSUMSI FASTFOOD DENGAN KEJADIAN OBESITAS PADA ANAK SD DI KOTA MANADO - Damapolii, Winarsi; Mayulu, Nelly; Masi, Gresty (JURNAL KEPERAWATAN)
Abstract: Obesity during childhood may be caused due to eating beyond need, lack of physical activity, and because of the excessive influence of food advertising. Today's lifestyle can also lead to obesity which is a trend likely to consume fast food or modern fast food such as burgers, pizza, fries Frenc peneletian aims to determine the relationship of fast food consumption with the incidence of obesity in primary school children in the city of Manado by using analytic survey research methods by using a cross sectional design (cross-sectional), using a test using the chi-square test (x2), at the 95% significance level (α 0,05). The results there is a relationship between fast food consumption relationship with the incidence of obesity in primary school children in the city of Manado with p = 0.024 conclusion Obesity prevalence in primary school children in the city of Manado in 2013 were 44 males (32.4%) and 24 women people (17.6%) fast food energy intake in children> average and 33.8% are obese and not obese at 23.5% There is a relationship between fast food consumption with the incidence of obesity in primary school children in the city of Manado p value = 0.024 suggestion Fast food is the cause of childhood obesity in this study should be a concern for policy makers to pay more attention to eating habits of children. The parents should be limiting children consume excessive amounts of snack foods or foods high in calories but low in fiber (fast food and junk food), and teaches healthy life and to get children exercising. Keywords: fast food, obesity Abstrak: Kegemukan saat anak-anak bisa disebabkan akibat makan melebihi kebutuhan, kurangaktivitas fisik, dan karena pengaruh iklan makanan yang berlebihan. Gaya hidup masa kini juga bisamenyebabkan kegemukan yaitu adanya kecenderungan suka mengkonsumsi makan cepat saji ataufast food modern seperti burger, pizza, frenc fries peneletian bertujuan Untuk mengetahui hubungan  konsumsi fast food dengan kejadian obesitas pada anak  SD di Kota Manado dengan menggunakan metode penelitian survei analitik dengan menggunakan  rancangan Cross sectional (potong lintang), dengan menggunakan uji menggunakan uji chi-square (x2), pada tingkat kemaknaan 95%   (α 0,05). Hasil penelitian ada hubungan antara hubungan  konsumsi fast food dengan kejadian obesitas pada anak  SD di Kota Manado dengan nilai p = 0,024 kesimpulan Prevalensi Obesitas pada anak SD di Kota Manado pada tahun 2013 adalah laki-laki 44 orang (32,4%)  dan perempuan 24 orang (17,6%) Asupan energi fast food pada anak > rata-rata  dan mengalami obesitas sebesar  33,8% dan tidak mengalami obesitas sebesar 23,5% Terdapat hubungan antara konsumsi fast food dengan kejadian obesitas pada Anak  SD di kota Manado dengan nilai p = 0,024 saran Fast food yang menjadi penyebab obesitas anak pada penelitian ini hendaknya menjadi perhatian bagi pengambil kebijakan untuk lebih memperhatikan kebiasaan makan anak. Pihak orang tua sebaiknya lebih membatasi anak mengkonsumsi makanan camilan dalam jumlah berlebih atau makanan yang tinggi kalori namun rendah serat (fast food dan junk food) serta mengajarkan hidup sehat dan membiasakan anak berolah raga. Kata kunci: fast food, obesitas